2005
DOI: 10.4049/jimmunol.174.4.2420
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Artemis Murine Counterpart Results in SCID and Defective V(D)J Recombination That Is Partially Corrected with Bone Marrow Transplantation

Abstract: Artemis is a mammalian protein, the absence of which results in SCID in Athabascan-speaking Native Americans (SCIDA). This novel protein has been implicated in DNA double-strand break repair and V(D)J recombination. We have cloned the Artemis murine counterpart, mArt, and generated a mouse with a targeted disruption of mArt. Artemis-deficient mice show a similar T−B− NK+ immunodeficiency phenotype, and carry a profound impairment in coding joint rearrangement, while retaining intact signal ends and close to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 25 publications
5
47
3
Order By: Relevance
“…Our original linkage study mapped the SCIDA genetic defect to chromosome 10p 13 and we subsequently identified a founder mutation in Artemis as the cause of SCIDA in Navajo and Apache Native Americans. 8,14 Surprisingly, this Artemis mutation was not found in the three T À B À NK þ SCID children from two related kindreds of Dine Indians in the Canadian Northwest Territories, a linguistically and genetically related people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our original linkage study mapped the SCIDA genetic defect to chromosome 10p 13 and we subsequently identified a founder mutation in Artemis as the cause of SCIDA in Navajo and Apache Native Americans. 8,14 Surprisingly, this Artemis mutation was not found in the three T À B À NK þ SCID children from two related kindreds of Dine Indians in the Canadian Northwest Territories, a linguistically and genetically related people.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of successful recombination was represented by the ratio of colonies grown on ampicillin and chloramphenicol (from recombined substrate only) vs ampicillin plates. 14 …”
Section: Egfp-based Inversional V(d)j Recombination Assaymentioning
confidence: 99%
“…Mice that lack Rag1 (REFS 45,46), Rag2 (REFS 47,48), Zap70 (REFS 49-53), Il7ra 54 or Dclre1c 55,56 show a severe defect in the production of T cells. These knockout mouse models accurately represent the alleles associated with severe disease in humans, but do not reflect the complex clinical presentation associated with alternative alleles.…”
Section: Antinuclear Antibodiesmentioning
confidence: 99%
“…Similarly, NHEJ factor gene inactivation in mice results in a profound impaired B-and T-cell development. [8][9][10][11][12][13][14] After completion of V(D)J recombination, mature immunoglobulin M ϩ (IgM ϩ ) B cells migrate to secondary lymphoid organs, where the immune B-cell repertoire is further shaped by 2 independent processes: somatic hypermutation and class switch recombination (CSR), which enhances the affinity and modifies the effector function of antibodies, respectively, without altering their antigenic specificity. CSR results in the replacement of the IgM constant region (C) with one of the downstream C H gene (␥, ⑀, or ␣) by a recombination mechanism between large repetitive switch (S) regions located upstream each constant region (except ␦), allowing for the fusion of the 2 S regions and excision of intervening DNA.…”
mentioning
confidence: 99%